Experimental study on the incident-angle-dependent laser coupling features of polystyrene targets. (12th October 2016) - Dong, Yunsong; Huang, Chengwu; Zhu, Tuo; Song, Tianming; Yang, Jiamin; Wei, Huiyue; Du, Huabing; Che, Xingsen; Mei, Yu
Abstract: Laser-produced plasmas have attracted great interest due to their potential utility in wide-ranging applications, especially in the field of inertial confinement fusion (ICF). For direct-driven ICF, laser coupling with polystyrene targets is a crucial and fundamental problem. In addition, oblique incidence is also a common phenomenon for laser facilities with multiple beams. It is necessary to evaluate the effects of oblique incidence on the laser coupling features relevant to the direct-driven ICF. Experiments using an intense nanosecond flat-top laser at around 4 × 10 14 W cm –2 to irradiate polystyrene planar targets from three different incidence angles have been performed on the Shenguang-III prototype laser facility. The time-integrated absolute values of the full aperture backscatter (FABS), near backscatter scattering (NBS), and the x-ray conversion efficiency (CE) have been measured quantitatively. According to the experimental results, with the increase of the incidence angle, the percentage of the stimulated Brillouin backscatter and the overall x-ray CE decreased while the stimulated Raman backscatter fraction rose. Theoretical analyses based on hydrodynamic simulations and linear theory were qualitatively consistent with the experimental results. In addition, the specularly reflected light was also observed at 30° laser oblique incidence.